SAT0111 Increased Insulin Resistance and Impaired Beta-Cell Function in Patients with Rheumatoid Arthritis: Could Inflammation Fully Explain These Metabolic Disturbances?. (15th July 2016) - Ristic, G.G.; Subota, V.; Stanisavljevic, D.; Glisic, B.; Petronijevic, M.; Stefanovic, D.
Abstract : Background: Chronic inflammation, the basic feature of rheumatoid arthritis (RA), plays a major role in accelerated atherosclerosis through its influence on insulin resistance (IR), lipid status, and other risk factors. Objectives: To investigate the level of IR and β-cell function in RA pts compared to healthy controls and evaluate whether inflammation can explain these metabolic disturbances. Methods: The study population included 127 nondiabetic subjects (90 RA pts and 37 matched healthy controls). We determined body mass index (BMI), waist circumference (WC), presence of hypertension and metabolic syndrome (MetS). All pts were on disease modifying antirheumatic drugs (93.3% on methotrexate), 65.6% on steroids (median 5 mg/day, range 5–10, none on steroids >10 mg/day), and 27.8% on biologic therapy. Laboratory analyses included inflammation markers (SE, hsCRP, IL-6), glucose, insulin, and C peptide (as a marker of insulin secretion). IR was calculated using the updated-computer Homeostasis Model Assessment (HOMA2-IR), based on fasting plasma glucose and specific insulin concentrations. Serum specific insulin was measured by a sensitive ELISA, which employs a monoclonal antibody to insulin. The output of the HOMA2 model was calibrated to give IR of 1 as normal. Therefore, values were considered abnormal when HOMA2-IR was >1. Results: Insulin resistance (HOMA2-IR>1) was detected in 67/90 (74.4%) of RA pts and in 20/37 (54.2%) of controls, p=0.025. RA pts had significantly higher concentration of specific insulin, C peptide and HOMA2-IR than healthy controls, while HOMA2-B was not statistically different. Importantly, both groups were comparable regarding all other factors known to affect glucose metabolism in the general population (age, WC, presence of hypertension or MetS). As it was expected we found significant differences in inflammation markers between RA pts and controls: ESR 29.5 (14–44) vs. 16.0 (10.0–20.0); hsCRP 5.5 (2.8–15) vs. 3.0 (1.8–3.9); IL-6; 7.4 (2.0–18.8) vs. 2.0 (2.0–2.4); p<0.000 for all. In logistic regression analysis, after adjustment for inflammation markers, statisticaly significant differences for HOMA2-IR and insulin became less important but still persisted (Table), while significance for C peptide disappeared. Conclusions: RA pts had higher IR and impaired β-cell function in comparison to healthy controls. The persistence of statistical significance for IR after correction for inflammation markers, may implicate that the influence of inflammatory disease burden is important but not the only risk factor for IR in RA. Disclosure of Interest: None declared